Bolstering Durability Skills of Educators and Occupational Commitment of Teachers in Public Elementary Schools - Canoy, Judy Marie N.; Baguio, Josephine B. (Asian Journal of Advanced Research and Reports, 2025)
This study aimed to examine the significant relationship between bolstering durability skills and occupational commitment among public elementary school teachers. A descriptive-correlational research design was employed, with 132 elementary school teachers from public schools in Malalag District, Division of Davao del Sur, participating as respondents of this study. Data were collected using adapted standardized questionnaires and analyzed using mean, standard deviation (SD), Pearson product-moment correlation, and multiple linear regression analyses. The results showed that both bolstering durability skills and occupational commitment were at very high levels among teachers. Correlation analysis revealed a strong positive relationship between bolstering durability skills and occupational commitment. Furthermore, multiple regression analysis indicated that among the domains of durability skills, supportive work environment, stress management, and sense of purpose and motivation significantly influenced occupational commitment, with supportive work environment having the strongest impact. Meanwhile, emotional resilience, adaptability and flexibility, and self-care and work-life balance were found to have no significant effect on occupational commitment. Based on these findings, it is recommended that school administrators prioritize creating supportive work environments, provide stress management resources, and foster teachers’ sense of purpose through motivation and professional development. These strategies may enhance teacher resilience, promote occupational commitment, and contribute to a more stable and effective educational workforce.